Short-term high-fat diet impacts bone material properties and metabolism for adult and aged C57BL/6JN mice - Kenna Brown; Ghazal Vahidi; Brady D. Hislop; Maya Moody; Steven Watson; Hope D. Welhaven; Ramina Behzad; Kat O. Paton; Lamya Karim; Ronald K. June; Stephen A. Martin; Chelsea M. Heveran (Communications Biology)
Abstract The elderly are at increased risk of bone fracture and more often consume poor quality diets, such as high-fat diet (HFD). We hypothesized that HFD exacerbates the loss of bone fracture resistance in aging. Female and male 5-month and 22-month C57BL/6JN mice were fed moderate HFD (45%) or low-fat diet (10%) for 8 weeks. All HFD groups showed disrupted glucose metabolism. Aging and HFD lowered bone fracture toughness, while aging alone reduced bone strength. Raman Spectroscopy demonstrated that aging and HFD differently impact bone matrix. Aging altered matrix properties but the effect depended on sex. Both sexes had higher carbonate content and altered collagen structure (I1670/I1690) with age but males also had increased crystallinity. HFD decreased mineral maturity (i.e., crystallinity) as well as altered collagen structure in females but not males. Untargeted metabolomics revealed that cortical tissue metabolism was dysregulated with aging and HFD. Aging and HFD affected pathways related to cellular function and viability, or glucose regulation, respectively. In aging mice, HFD also impacted osteoclast and adipocyte abundance and osteocyte viability in both sexes. Together, these data demonstrate that HFD exacerbates the loss of bone matrix quality and fracture resistance in aging C57BL/6JN mice.